Literature Review: Multiparadigm Accounting Research - Danny Ivan Rantung; Nouke Sysca Oroh; Ika Prayanthi (Universitas Islam Islam Sumatera Utara, 2022)
The objective of this paper is to explore all related literature with multiparadigm accounting research approaches. The literature search strategy begins by looking at literature from sources in the forms of books or sources originating from several databases or search engines including open knowledge maps, google scholar, and z-library. The keywords used for the search are “accounting: science with various paradigms, multiparadigm accounting research, accounting paradigm and paradigm accounting”. From the results of searching and reviewing the literature, including books, journal articles and other electronic sources, various kinds of multiparadigm accounting research were obtained. By knowing the benefits of each of the paradigm viewpoints that have been described, it is good if we take a mixed paradigm approach in accounting research so that research results are of higher quality because they are not only based on one paradigm. Even though in one research using one accounting paradigm, those of us who strongly believe in a certain paradigm still have an open mind towards other paradigms thus enriching our views so that in studying accounting all paradigms are believed to complement one another. This research will greatly contribute to academics in viewing accounting from various perspectives. This literature review classifies multiparadigm accounting research based on more specific groups.